Acupuncture versus sham acupuncture for chronic prostatitis/chronic pelvic pain. - Lee, S; Liong, M; Yuen, K; Leong, W; Chee, C; Cheah, P; Choong, W; Wu, Y; Khan, N; Choong, W; Yap, H; Krieger, J (2008)
BACKGROUND: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) afflicts 2%-10% of adult men. Available therapies offer little or no proven benefit. Because acupuncture represents an attractive "natural" therapy, we compared the efficacy of acupuncture to sham acupuncture for CP/CPPS. METHODS: Participants met US National Institutes of Health (NIH) consensus criteria for CP/CPPS, were aged > or = 20 years old, and had a total score > or = 15 on the NIH Chronic Prostatitis Symptom Index (NIH-CPSI) and symptoms for at least 3 of the preceding 6 months. They were randomized 1:1 to acupuncture or sham acupuncture. Treatment consisted of twice-weekly 30-minute sessions for 10 weeks (20 sessions total) without needle stimulation, herbs, or adjuvants. The primary response criterion was a 6-point decrease from baseline to week 10 in NIH-CPSI total score (range 0-43). RESULTS: Thirty-two (73%) of 44 participants responded in the acupuncture group compared with 21 (47%) of 45 sham group participants (relative risk 1.81, 95% confidence interval, 1.3-3.1, P = .02). Long-term responses 24 weeks after completing therapy without additional treatment occurred in 14 (32%) of 44 acupuncture group participants and in 6 (13%) of 45 sham group participants (relative risk 2.39, 95% confidence interval, 1.0-5.6, P = .04). CONCLUSIONS: After 10 weeks of treatment, acupuncture proved almost twice as likely as sham treatment to improve CP/CPPS symptoms. Participants receiving acupuncture were 2.4-fold more likely to experience long-term benefit than were participants receiving sham acupuncture.